Exploring the pathophysiological mechanisms and wet biomarkers of VPS13A disease - Jingqi Lin; Hongmei Meng; Nilupaer Shafeng; Jiaai Li; Huaiyu Sun; Xi Yang; Zhiqing Chen; Shuai Hou (Frontiers in Neurology, 2024)
VPS13A disease (also known as Chorea-Acanthocytosis, ChAc) is a representative subtype of the neuroacanthocytosis (NA) syndromes, characterized by neurodegeneration in the central nervous system and acanthocytosis in peripheral blood. It is a rare autosomal recessive genetic disorder caused by loss-of-function variants in the VPS13A gene, which is currently the only known pathogenic gene for ChAc. VPS13A protein is a member of novel bridge-like lipid transfer proteins family located at membrane contact sites, forming direct channels for lipid transport. The specific mechanism underlying how the loss of VPS13A function leads to the hematological and neurological phenotypes of the disease remains unclear. Here we present a review of recent studies on VPS13A protein and ChAc, focusing on the potential role of the VPS13A protein in pathophysiology of ChAc and also review the known and potential wet biomarkers of ChAc to enhance our comprehension of this rare disease.